Comparative Study of the Analgesic Efficacy of Rectal Tramadol versus Intravenous Tramadol for Inguinal Hernia Repair Surgery - Jose B Cherayath; Jitin George (Academia Anesthesiologica International, 2019)
Background: There is uncertainity observed in selection of optimal method for intra and post operative administration of analgesics for inguinal hernia repair surgery. Aim: This study was performed to evaluate and differentiate the analgesic efficacy of tramadol via intravenous and rectal administration for inguinal hernia repair.Subjects and Methods: This study is a prospective, randomised, hospital based, single blinded study. All 50 patients were divided into 2 groups of 25 each namely group A and Group B. Group A received intravenous tramadol hydrochloride (1.5 mg/kg) and group B received tramadol (1.5mg/kg) in the form of suppository.Results: In the rectally administered tramadol, the analgesia duration is prolonged which further reduces the rescue analgesia requirement. Compared to intravenously administered tramadol, patient comfort is more in rectally administered tramadol as nausea and vomiting postoperatively is avoided.Conclusion: This study concludes that rectally administering tramadol is safer, easier, more reliable, non-invasive, more comfortable and painless compared to intravenously administered tramadol.